Development of Electronic Student Worksheets (E-LKPD) Based on Flipbook - Sujinah; Rohmah Barokah Toriqul Yanah (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
Student-centered learning serves as the primary foundation in the educational process. Analyzing the structure of scientific works is a critical component in Indonesian language instruction at Phase F. Through the implementation of student-centered learning, educators can utilize technology to enhance the learning process and develop engaging teaching materials. This study aims to describe the effectiveness of electronic student worksheets (E-LKPD) assisted by flipbooks in teaching the analysis of scientific works. This developmental research employs a qualitative descriptive approach, focusing on the eleventh-grade students of SMKN 4 Surabaya. The validation results of the E-LKPD indicate an 82% feasibility score, as assessed by subject matter experts. Student responses to the flipbook-assisted E-LKPD for analyzing the structure of scientific works show an 85.6% effectiveness rate. Moreover, 98.5% of students reported that the flipbook-based E-LKPD significantly aided their understanding of the structure of scientific works on the theme of nature conservation. A key factor contributing to this preference is the extensive benefits students gain as valuable preparation for their future lives.